Time-Dependent Global Attractor for a Class of Nonclassical Parabolic Equations - Fang-hong Zhang (Journal of Applied Mathematics)
Based on the recent theory of time-dependent global attractors in the works of Conti et al. (2013) and di Plinio et al. (2011), we prove the existence of time-dependent global attractors as well as the regularity of the time-dependent global attractor for a class of nonclassical parabolic equations.